How do you solve the system using the elimination method for $ 3x+y=5 $ and $ x-2y=4? $
Answer
Verified
443.4k+ views
Hint: Here two equations are given which we have to solve by using elimination method. ‘
In this method we have to make one of the coefficients or variables equal for both of the equations.
After making it equal, that coefficient or variable gets cancelled while performing adding or subtracting.
Complete step by step solution:
The given equation we have to solve by using elimination method.
The equation given are:
$ 3x+y=5...(i) $
$ x-2y=4...(ii) $
Now, we have to make the $ y $ coefficient equal for both the equations.
For that we have to multiply the equation $ (i) $ by $ 2 $ then we will get,
So,
$ 2\times \left( 3x+y=5 \right) $
$ 6x+2y=10...(iii) $
Now, the equation $ (ii) $ and equation $ (iii) $ have equal $ y $ coefficient with opposite sign, So then it can be cancelled while adding.
So, add equation $ (ii) $ and equation $ (iii) $
$ \left( x-2y=4 \right)+\left( 6x+2y=10 \right) $
$ =7x=14 $
$\Rightarrow x=\dfrac{14}{7} $
$\Rightarrow x=2 $
Put, the $ x=2 $ in equation $ (i) $
$ 3x+y=5 $ (given)
$\Rightarrow 3\times 2+y=5 $
$ \Rightarrow6+y=5 $
Transpose the $ 6 $ to other side of equation
$ y=5-6 $
$\Rightarrow y=-1 $
Therefore the solution of given equation by elimination method is $ x=2 $ and $ y=-1 $
Additional Information:
There are so many methods of solving the system of equations.
But two of them are most preferable, one is elimination and second is substitution. The elimination method is that, in which we have to add or subtract the given equation for getting an answer of the equation in one variable. In the substitution method, from one equation, the other value of one variable is substituted in another equation.
Note: In equation $ (iii) $ we multiply it by $ 2 $ for making the equal $ y- $ coefficient. We can either make the equal $ x $ coefficient of equation $ (i) $ and equation $ (ii) $ . It is done because both the equations have different $ x $ and $ y $ coefficients but for simplifying and further calculation we have to make one of the coefficients equal. Either $ x $ or $ y $ for both the equations.
The calculated solutions can be verified to check whether it satisfies the equation or not which is as follows.
Put $ x=2 $ and $ y=-1 $ in equation $ (i) $
$ 3x+y=5 $
$\Rightarrow 3\times 2+\left( -1 \right)=5 $
$\Rightarrow 6-1=5 $
$ 5=5 $
Now, put $ x=2 $ and $ y=-1 $ in equation $ (ii) $
$ x-2y=4 $
$\Rightarrow 2-2\left( -1 \right)=4 $
$ \Rightarrow2+2=4 $
$ 4=4 $
Hence from the above calculation, the solutions are satisfied by both the equations, therefore the solutions calculated are correct.
In this method we have to make one of the coefficients or variables equal for both of the equations.
After making it equal, that coefficient or variable gets cancelled while performing adding or subtracting.
Complete step by step solution:
The given equation we have to solve by using elimination method.
The equation given are:
$ 3x+y=5...(i) $
$ x-2y=4...(ii) $
Now, we have to make the $ y $ coefficient equal for both the equations.
For that we have to multiply the equation $ (i) $ by $ 2 $ then we will get,
So,
$ 2\times \left( 3x+y=5 \right) $
$ 6x+2y=10...(iii) $
Now, the equation $ (ii) $ and equation $ (iii) $ have equal $ y $ coefficient with opposite sign, So then it can be cancelled while adding.
So, add equation $ (ii) $ and equation $ (iii) $
$ \left( x-2y=4 \right)+\left( 6x+2y=10 \right) $
$ =7x=14 $
$\Rightarrow x=\dfrac{14}{7} $
$\Rightarrow x=2 $
Put, the $ x=2 $ in equation $ (i) $
$ 3x+y=5 $ (given)
$\Rightarrow 3\times 2+y=5 $
$ \Rightarrow6+y=5 $
Transpose the $ 6 $ to other side of equation
$ y=5-6 $
$\Rightarrow y=-1 $
Therefore the solution of given equation by elimination method is $ x=2 $ and $ y=-1 $
Additional Information:
There are so many methods of solving the system of equations.
But two of them are most preferable, one is elimination and second is substitution. The elimination method is that, in which we have to add or subtract the given equation for getting an answer of the equation in one variable. In the substitution method, from one equation, the other value of one variable is substituted in another equation.
Note: In equation $ (iii) $ we multiply it by $ 2 $ for making the equal $ y- $ coefficient. We can either make the equal $ x $ coefficient of equation $ (i) $ and equation $ (ii) $ . It is done because both the equations have different $ x $ and $ y $ coefficients but for simplifying and further calculation we have to make one of the coefficients equal. Either $ x $ or $ y $ for both the equations.
The calculated solutions can be verified to check whether it satisfies the equation or not which is as follows.
Put $ x=2 $ and $ y=-1 $ in equation $ (i) $
$ 3x+y=5 $
$\Rightarrow 3\times 2+\left( -1 \right)=5 $
$\Rightarrow 6-1=5 $
$ 5=5 $
Now, put $ x=2 $ and $ y=-1 $ in equation $ (ii) $
$ x-2y=4 $
$\Rightarrow 2-2\left( -1 \right)=4 $
$ \Rightarrow2+2=4 $
$ 4=4 $
Hence from the above calculation, the solutions are satisfied by both the equations, therefore the solutions calculated are correct.
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE
Write an application to the principal requesting five class 10 english CBSE